2022
DOI: 10.1097/fbp.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Male and female rats exhibit comparable gaping behavior but activate brain regions differently during expression of conditioned nausea

Abstract: Twenty-five to fifty percent of patients undergoing chemotherapy will develop anticipatory nausea and vomiting (ANV), in which symptoms occur in anticipation of treatment. ANV is triggered by environmental cues and shows little response to traditional antiemetic therapy, suggesting that unique neural pathways mediate this response. Understanding the underlying neural mechanisms of this disorder is critical to the development of novel therapeutic interventions. The purpose of the present study was to identify b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…Our findings revealed similar activated brain regions in nocebo nausea, particularly those primarily responsible for integrating cognition, emotion, and nausea messages, such as the ACC, insula, BLA, PVN, PVT, PAG, DRD, and NTS. This was in line with a recent study that detected c‐Fos expression in different brain regions after inducing conditioned nausea in male rats, with more activated neurons in the frontal cortex, insula, and PVN 50 . The ACC and insula, the key brain regions identified in our study, could integrate emotional and cognitive stimuli to directly trigger nausea 12,51 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings revealed similar activated brain regions in nocebo nausea, particularly those primarily responsible for integrating cognition, emotion, and nausea messages, such as the ACC, insula, BLA, PVN, PVT, PAG, DRD, and NTS. This was in line with a recent study that detected c‐Fos expression in different brain regions after inducing conditioned nausea in male rats, with more activated neurons in the frontal cortex, insula, and PVN 50 . The ACC and insula, the key brain regions identified in our study, could integrate emotional and cognitive stimuli to directly trigger nausea 12,51 .…”
Section: Discussionsupporting
confidence: 93%
“…This was in line with a recent study that detected c‐Fos expression in different brain regions after inducing conditioned nausea in male rats, with more activated neurons in the frontal cortex, insula, and PVN. 50 The ACC and insula, the key brain regions identified in our study, could integrate emotional and cognitive stimuli to directly trigger nausea. 12 , 51 Strong evidence also suggested that they were associated with the production of aversion emotions.…”
Section: Discussionmentioning
confidence: 74%